2020
DOI: 10.1128/msystems.00396-20
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Bacterial Pathways Influence the Efficacy of Antibiotics against Mycobacterium tuberculosis

Abstract: Effective tuberculosis treatment requires at least 6 months of combination therapy. Alterations in the physiological state of the bacterium during infection are thought to reduce drug efficacy and prolong the necessary treatment period, but the nature of these adaptations remain incompletely defined. To identify specific bacterial functions that limit drug effects during infection, we employed a comprehensive genetic screening approach to identify mutants with altered susceptibility to the first-line antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 68 publications
10
79
0
Order By: Relevance
“…The relative representation of each Mtb mutant in the input pool versus the pools recovered from mouse spleens was quantified ( Table S4). Consistent with our previous work (Bellerose et al, 2020;, we identified 234 Mtb genes that are required for growth or survival in Mtb in B6 mice, based on significant underrepresentation of the corresponding mutant after four weeks of in vivo selection. All but one of these genes were found to be required in the larger panel, increasing confidence in this Mtb gene set ( Figure 4A and 4B).…”
Section: Tipqtl Define Genetic Variants That Control Tb Immunophenotypessupporting
confidence: 87%
See 3 more Smart Citations
“…The relative representation of each Mtb mutant in the input pool versus the pools recovered from mouse spleens was quantified ( Table S4). Consistent with our previous work (Bellerose et al, 2020;, we identified 234 Mtb genes that are required for growth or survival in Mtb in B6 mice, based on significant underrepresentation of the corresponding mutant after four weeks of in vivo selection. All but one of these genes were found to be required in the larger panel, increasing confidence in this Mtb gene set ( Figure 4A and 4B).…”
Section: Tipqtl Define Genetic Variants That Control Tb Immunophenotypessupporting
confidence: 87%
“…To characterize the diversity of disease states that are possible in a genetically diverse mouse population, we infected a panel of 52 CC lines and the founder strains with Mtb. To enable TnSeq studies, the animals were infected via the intravenous route with a saturated library of Mtb transposon mutants, which in sum produce an infection that is similar to the wild-type parental strain (Bellerose et al, 2020;.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several Mtb mutants displayed altered susceptibility to TB drugs in the murine model of TB disease, many of which were associated with CW pathways described herein. The findings suggest that genetic variants that may be associated with drug resistance in clinical Mtb isolates do not alter in vitro drug susceptibility but can still influence drug efficacy in vivo ( Bellerose et al., 2020 ). This suggested that the genetic backgrounds of different clinical strains can impact the applicability of new anti-mycobacterial drugs in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%